Novel paddle stroke analysis for elite slalom kayakers: Relationship with force parameters - Dalcheco Messias, L. H.; de Barros Sousa, F. A.; Masseli dos Reis, I. G.; Ferrari, H. G.; Gobatto, C. A.; Caputo Saldanha Serra, C.; Papoti, M.; Barros Manchado-Gobatto, F. (PLOS ONE, 2018)
This study was divided into two complementary parts. In Part 1, we proposed a novel paddle strokes analysis based on the force signal from a 30-s all-out tethered test; and compared these results with video recordings. In Part 2, we investigated the relationship between force data from the same test with paddle stroke results from both methods. Eleven male elite slalom kayakers (Brazilian national team) were evaluated. The tethered test was conducted for force parameters analysis (peak-force, mean-force, impulse). Video recording analysis was conducted, and the performed strokes (V.NumberPaddle) was counted and frequency (V.FrequencyPaddle) calculated by the V.NumberPaddle divided by 30 (i.e. total time of test). The new method consisted of performed strokes and frequency achievement from a load cell force signal analysis (S.NumberPaddle and S.FrequencyPaddle, respectively). Paired test-t did not show difference between methods results, but significant correlations were only obtained for the number of paddle strokes. Force parameters were only correlated with S.NumberPaddle and S.FrequencyPaddle. Overall, considering the theoretical and practical application, we propose that the new method should be used as an alternative to the video recording.